Activated Platelets Interfere with Recruitment of Mesenchymal Stem Cells to Apoptotic Cardiac Cells via High Mobility Group Box 1/Toll-like Receptor 4-mediated Down-regulation of Hepatocyte Growth Factor Receptor MET - Vogel, Sebastian (American Society for Biochemistry and Molecular Biology, 2014)
Recruitment of mesenchymal stem cells (MSC) following cardiac injury, such as myocardial infarction, plays a critical role in tissue repair and may contribute to myocardial recovery. However, the mechanisms that regulate migration of MSC to the site of tissue damage remain elusive. Here, we demonstrate in vitro that activated platelets substantially inhibit recruitment of MSC toward apoptotic cardiac myocytes and fibroblasts. The alarmin high mobility group box 1 (HMGB1) was released by platelets upon activation and mediated inhibition of the cell death-dependent migratory response through Toll-like receptor (TLR)-4 expressed on the MSC. Migration of MSC to apoptotic cardiac myocytes and fibroblasts was driven by hepatocyte growth factor (HGF), and platelet activation was followed by HMGB1/TLR-4-dependent down-regulation of HGF receptor MET on MSC, thereby impairing HGF-driven MSC recruitment. We identify a novel mechanism by which platelets, upon activation, interfere with MSC recruitment to apoptotic cardiac cells, a process that may be of particular relevance for myocardial repair and regeneration.